Investor Risk Behavior Moderation in Financial Literacy on Millennial Investment Decisions - Mongan, Claudio Julio; Halik, Johannes Baptista; Lambe, Kristian Hoegh Pride; Irdawati (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2025)
Research aim : This study examines the moderating role of investor risk behavior in the relationship between financial literacy and investment decisions among millennials. Design/Methode/Approach : A quantitative approach was employed, collecting data from 96 millennial investors through a structured survey. Structural Equation Modeling-Partial Least Squares (SEM-PLS) was utilized to analyze both direct and indirect relationships among variables. Research Finding : The findings indicate that financial literacy does not significantly influence investment decisions. However, financial literacy has a positive and significant impact on investor risk behavior, which, in turn, significantly influences investment decisions. Furthermore, investor risk behavior moderates the relationship between financial literacy and investment decisions in a positive and significant manner. Theoretical contribution/Originality : These results highlight the critical role of risk behavior as both a mediating and moderating mechanism in leveraging financial literacy for improved investment decision-making. Practitioner/Policy implication : The study's practical implications suggest that financial literacy programs should not only focus on enhancing knowledge but also on fostering risk management skills to support informed investment choices. Research limitation : This study is limited by its relatively small sample size and geographic focus on Makassar City, which may restrict the generalizability of the findings to broader populations. Additionally, the cross-sectional design captures only a snapshot of behavior, making it difficult to infer long-term patterns or causal relationships.